Building Mental Well-being through Physical Literacy: The Role of Physical Activity from an Embodied Cognition Perspective - Sopyan Sauri; Herman Subarjah; Fauzi Setiadi Firdaus; Tomi Efendi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study examines the relationship between Physical Literacy (PL) and mental well-being among university students, with physical activity functioning as a mediating variable through the Embodied Cognition framework. A cross-sectional study was conducted with 195 active students from the Faculty of Sports and Health Education at Universitas Pendidikan Indonesia, Bandung. Data were collected using the Student Physical Literacy Questionnaire, the International Physical Activity Questionnaire-Short Form (IPAQ-SF), and the Student Well-being Scale. Mediation analysis was performed using PROCESS Macro for SPSS version 4.2, Model 4. Results revealed that PL significantly predicts physical activity (β = 0.27, p < 0.005), and both PL and physical activity significantly influence mental well-being (β = 0.21 and β = 0.36 respectively, p < 0.005). The total effect of PL on mental well-being was 0.40 (p < 0.005), consisting of a direct effect of 0.27 (67.5%) and an indirect effect through physical activity of 0.13 (32.5%). Bootstrap confidence intervals (0.06-0.21) confirmed significant partial mediation. The findings affirm the embodied cognition perspective, suggesting that physical literacy plays an essential role in promoting mental well-being both directly and through  physical activity. This study provides empirical evidence for integrating physical literacy development into mental health promotion strategies within higher education contexts.